Commission on audit a case study on employees' satisfaction with the interior design of their workplace - Soco, Clarisse Marie A.
The study sought to determine whether or not the employees of a selected local government office are satisfied with their workplace and whether or not their office's interior design contributes to their job satisfaction and productivity. It also evaluated whether or not the design of the workplace works well with Filipino values. The research used a twofold approach which included both quantitative and qualitative means of data gathering. The instruments used were on-site pictures of the workplace, floor plan, and questionnaire. The answers were evaluated with the use of ratio analysis. A total of forty five (45) employees were included in the study. Results showed that the office directors magnified a Western concept of privacy where preference for isolation and individualism was emphasized. On the other hand, the non-managerial staff members preferred to be around their co-workers describing a groupist form of behavior. Findings inferred that the concept of personalism was also manifested in the workplace. The workspace of the directors was not fully enclosed and private. The bearing of nameplates on their desks served as a distinction from the non-managerial staff and it gave them the feeling of authority. Collectivity was found to be an important work value among the employees. While the directors preferred to be isolated as a result of modern education, the non-managerial staff emphasized the importance of interacting with co-employees. The study concluded that the respondents are satisfied with the over-all design of their workplace. However certain characteristics of the workplace were found to be problematic such as privacy. It is recommended that the management should recognize work values of the employees in order to effectively work in the office.